The Ferroquine Antimalarial Conundrum: Redox Activation and Reinvasion Inhibition1. Issue 30 (13th June 2013) - Dubar, Faustine; Slomianny, Christian; Khalife, Jamal; Dive, Daniel; Kalamou, Hadidjatou; Guérardel, Yann; Grellier, Philippe; Biot, Christophe
<x xml:space="preserve">Abstract</x> Metal health: Ferroquine is a ferrocene‐based analogue of the antimalarial drug chloroquine. In addition to the primary mechanism of quinoline action, fluorescent probe studies in infected red blood cells show another mechanism is at work. It is based on the production of HO. in the acidic and oxidizing environment of the digestive vacuole of the malaria parasite and implies that, with ferroquine, reinvasion can be inhibited.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>